2020
DOI: 10.12659/ajcr.926694
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Case Report: An 84-Year-Old Man with Exacerbation of Multiple Comorbidities Due to COVID-19 Managed by a Multidisciplinary Team Using Patient-Reported Outcomes

Abstract: Patient: Male, 84-year-old Final Diagnosis: Acute bronchitis • chronic multiple pain with spondylosis with radiculopathy: lumbar region • chronic renal failure CKD 4 • derailed type 2 diabetes mellitus • diabetes mellitus type 2 • eart failure • hyperuricaemia • progressive aortic stenosis • pulmonary hypertension • SARS-CoV2 Symptoms: Appetite loss • fever • pain • sore throat Medication: — Clinical Procedure: — Specialty: General and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Eleanor M. Rees et al carried out systematic analysis and proposed that the bed demand of emergency plan ccould be simulated by LoS, so as to predict the demand of health resources [9]. Knowledge on factors affecting hospital LoS is evolving, and some studies reported that LoS of COVID-19 patients might be affected by the severity of disease, medication, comorbidity and other factors [10][11][12]. However, most reported risk factors related to LoS were clinical predictors and the role of social determinants were still unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Eleanor M. Rees et al carried out systematic analysis and proposed that the bed demand of emergency plan ccould be simulated by LoS, so as to predict the demand of health resources [9]. Knowledge on factors affecting hospital LoS is evolving, and some studies reported that LoS of COVID-19 patients might be affected by the severity of disease, medication, comorbidity and other factors [10][11][12]. However, most reported risk factors related to LoS were clinical predictors and the role of social determinants were still unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these few studies, there is little research on how people living through the COVID-19 crisis or those having been infected with the disease perceive and experience the situation [10]. Of particular interest for exploration are the views and experiences of people with chronic pain, as COVID-19 can have a greater impact on them [11], as well as on individuals with physical disabilities in general [3].…”
Section: Introductionmentioning
confidence: 99%
“… 7 9 Although the clinical presentation for SARS-CoV-2 varies from mild to moderate respiratory illness, older people with pre-existing conditions, such as diabetes, chronic respiratory disease, cardiovascular disease, and cancer are more likely to develop a serious illness with complications and death. 10 This has posed challenges in halting the transmission via droplets due to asymptomatic carriers as well as identifying drugs that might be effective in treating patients who can potentially decompensate later in the clinical course. 11 Consequently, as of off-label use, some existing drugs have been given to patients with COVID-19, including anti-HIV, anti-influenza, and anti-malaria agents.…”
Section: Introductionmentioning
confidence: 99%